Ideas, Images, and Methods of Portrayal: Insights into Classical Arabic Literature and Islam by Sebastian Günther, ed. (Leiden, Boston: Brill, 2005. 468 pages.) (American Journal of Islam and Society, 2007)
This ambitious collection of sixteen essays (plus an introduction by the editor)ranges widely across Islamic history and scholarly disciplines. The unifyingtheme is reflected in the title: Muslim texts are examined for their conceptualframeworks as conveyers of a cultural ethos. While some essays aremore successful than others in enunciating this theme’s more theoreticalaspects, the range of topics covered means that most readers will find somethingof interest and relevance and will likely be stimulated to apply themethods of analysis to their own area of study.Sebastian Günther’s introduction does an admirable job of highlightingeach essay’s contribution to creating an overall picture of Muslim intellectualhistory and the “cultural specificity of Islam that facilitated theadvancement of intellectual life and the formation of ‘modern’ societies”(p. xiv) by paying attention to the ideas, forms, content, and impact of textualartefacts from the eighth through the fourteenth centuries.Stephan Dähne begins the volume by focusing on the Qur’an and itsuse in political speeches attributed to Abu Hamza al-Shari (d. 747),Abdullah ibn al-Zubayr (d. 692), Uthman ibn Hayyan al-Murri (d. after713), and Abdallah ibn Tahir (d. 844). Ute Pietruschka then deals with theChristian community’s literary activity under the Umayyads as it developedin Syriac (and emerged in Arabic), maintained the Byzantine tradition,and was impacted by Islam. Keeping with the Christian theme, SandraToenies Keating discusses the work of the Christian apologist Abu Ra’ita(d. ca 835) and his attempt to defend Biblical scripture from the Muslimcharge of falsification (tahrif) ...